Clinicopathological, immune and molecular correlates of PD-L2 methylation in gastric adenocarcinomas. (1st March 2019) - Lingohr, Philipp; Dohmen, Jonas; Semaan, Alexander; Branchi, Vittorio; Dietrich, Jörn; Bootz, Friedrich; Kalff, Jörg C; Matthaei, Hanno; Dietrich, Dimo
Aim: We investigated the significance of PD-L2 DNA methylation in gastric adenocarcinomas.Methods: We analyzed the methylation at different CpG sites within the PD-L2-encoding gene PDCD1LG2 with regard to correlations and associations with gene expression, clinicopathological parameters, molecular features and immune cell infiltrates in two publicly available cohorts (The Cancer Genome Atlas and Singapore cohorts) of a total of 594 gastric adenocarcinoma patients.Results: PD-L2 methylation is significantly associated with transcriptional activity, survival, Epstein–Barr virus infection, PD-L2 gene amplification, CD8 + T-cell infiltration, microsatellite instability and high mutational load (tumor mutational burden, hypermutation).Conclusion: PD-L2 methylation is associated with known predictive biomarkers of response to anti-PD-1 immunotherapies.